Long COVID in cancer patients: preponderance of symptoms in majority of patients over long time period - Hiba Dagher; Anne-Marie Chaftari; Ishwaria M Subbiah; Alexandre E Malek; Ying Jiang; Peter Lamie; Bruno Granwehr; Teny John; Eduardo Yepez; Jovan Borjan; Cielito Reyes-Gibby; Mary Flores; et al. (eLife, 2023)
Background: An increasing number of observational studies have reported the persistence of symptoms following recovery from acute COVID-19 disease in non-cancer patients. The long-term consequences of COVID-19 are not fully understood particularly in the cancer patient population. The purpose of this study is to assess post-acute sequelae of SARS-CoV-2 infection (PASC) in cancer patients following acute COVID-19 recovery. Methods: We identified cancer patients at MD Anderson Cancer Center who were diagnosed with COVID-19 disease between March 1, 2020, and September 1, 2020, and followed them till May 2021. To assess PASC, we collected patients reported outcomes through questionnaires that were sent to patients daily for 14 days after COVID-19 diagnosis then weekly for 3 months, and then monthly thereafter. We also reviewed patients’ electronic medical records to capture the persistence or emergence of new COVID19-related symptoms reported during any clinic or hospital encounter beyond 30 days of the acute illness and up to 14 months. Results: We included 312 cancer patients with a median age of 57 years (18–86). The majority of patients had solid tumors (75%). Of the 312 patients, 188 (60%) reported long COVID-19 symptoms with a median duration of 7 months and up to 14 months after COVID-19 diagnosis. The most common symptoms reported included fatigue (82%), sleep disturbances (78%), myalgias (67%), and gastrointestinal symptoms (61%), followed by headache, altered smell or taste, dyspnea (47%), and cough (46%). A higher number of females reported a persistence of symptoms compared to males (63% vs. 37%; p=0.036). Cancer type, neutropenia, lymphocytopenia, and hospital admission during acute COVID-19 disease were comparable in both groups. Among the 188 patients with PASC, only 16 (8.5%) were re-admitted for COVID-related reasons. Conclusions: More than one out of two cancer patients, and more likely females, report PASC that may persist beyond 6 months and even 1 year. The most common symptoms are non-respiratory and consist of fatigue, sleep disturbance, myalgia, and gastrointestinal symptoms. Most of the cancer patients with PASC were managed on outpatient basis with only 8.5% requiring a COVID-19-related re-admission. Funding: This research is supported by the National Institutes of Health/National Cancer Institute under award number P30CA016672, which supports the MD Anderson Cancer Center Clinical Trials Office. The funders had no role in study design, data collection, and interpretation, or the decision to submit the work for publication.